Real and Financial Vulnerabilities from Crossborder Banking Linkages - Kim, Kyunghun (IMF Working Papers; Working Paper ;, 2014)
This paper looks at the vulnerabilities stemming from banking sector linkages between countries and their macroeconomic effects. It finds that credit risks (from a banking system's claims on other countries) and funding risks (from a banking system's liabilities to another) have declined over the past five years. It also finds that funding vulnerabilities have real effects. During normal times, funding vulnerabilities are associated with significant positive GDP growth surprises. During crisis times, funding vulnerabilities are associated with significant negative GDP growth surprises. The results tell us that policymakers should pay more attention to understanding crossborder funding risks.